A Discourse on Abandoned Housing Projects (AHPs) and the Potential of Crowdfunding: Malaysian Evidence - Mohd Thas Thaker, Hassanudin (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2025)
The surge in housing demand has exacerbated challenges in Malaysia's property market, notably the widespread issue of abandoned housing projects (AHPs). Despite the government and banking sector's continuous efforts to facilitate financing for affordable housing, the increasing number of AHPs indicates economic inefficiencies. Literature identifies developers' financing constraints as a key driver of project abandonment. To address this, our study proposes the